1980
DOI: 10.1002/chin.198051078
|View full text |Cite
|
Sign up to set email alerts
|

ChemInform Abstract: MELANIN. 2. ELECTROCHEMICAL STUDY OF THE OXIDATION OF α‐METHYLDOPA AND 5,6‐DIHYDROXY‐2‐METHYLINDOLE

Abstract: α‐Methyldopa (Ia) und Dopa (Ib) werden der elektrochemischen Oxidation unterworfen und über zahlreiche diskutierte Zwischenstufen wie (II) und (III) in die Dihydroxy‐indole (IV) sowie melanoide Pigmente übergeführt.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 1 publication
1
1
0
Order By: Relevance
“…According to the literature, experimental barriers (at 298 K) for the intramolecular cyclization of dopaquinone (ΔG ‡ = 62.3 kJ/mol) and dopamine quinone (ΔG ‡ = 64.8 kJ/mol) are very similar. 55,56 These experimental data are reproduced at the SMD-M06L/ 6-31+G(d,p)/LANL2DZ level of theory (ΔG ‡ = 63.3 and 58.9 kJ/mol, respectively; see Scheme 4), which confirms that intrinsic cyclization rates are comparable and relatively rapid in both cases. The rate-determining step of cyclization involves the unprotonated form of the amino group, and therefore the reaction rate is strongly pH dependent.…”
Section: ■ Introductionsupporting
confidence: 58%
“…According to the literature, experimental barriers (at 298 K) for the intramolecular cyclization of dopaquinone (ΔG ‡ = 62.3 kJ/mol) and dopamine quinone (ΔG ‡ = 64.8 kJ/mol) are very similar. 55,56 These experimental data are reproduced at the SMD-M06L/ 6-31+G(d,p)/LANL2DZ level of theory (ΔG ‡ = 63.3 and 58.9 kJ/mol, respectively; see Scheme 4), which confirms that intrinsic cyclization rates are comparable and relatively rapid in both cases. The rate-determining step of cyclization involves the unprotonated form of the amino group, and therefore the reaction rate is strongly pH dependent.…”
Section: ■ Introductionsupporting
confidence: 58%
“…49 Or they also did by using an authentic sample of 5. 53 Hawley et al observed the oxidation peak due to 5,6-dihydroxy-N-methylindole from the adrenaline pathway. 48 In our case, barely discernible peaks due to 5 ⇀ 6 at −0.026 V were observed at pH 7.7 and 8.0 in DPV.…”
Section: Ece Study Of Dopamine At Long-length Cnt Electrodementioning
confidence: 99%